Heavy Metal Pollution Status in The Main Surface Waters of The N'djili River Basin in Kinshasa, Democratic Republic of Congo: A Review with Application and Evaluation of Pollution Indices Evaluation - Nzomba, Daniel Nzomba wa (Indonesian Journal of Earth Sciences, 2024)
The aim of this study was to assess heavy metal pollution in the surface waters of the N'djili river watershed, as well as to determine the main sources of this pollution and their impact on water quality. Five sampling sites were selected in the watershed, representing a variety of urban and industrial influences. In these samples, trace metals such as lead (Pb), cadmium (Cd) and arsenic (As) were measured by atomic absorption spectrometry. The respective mean concentrations of lead (Pb), cadmium (Cd) and arsenic (As) in the surface waters of the N'djili basin are 0.066 mg/L, 0.006 mg/L and 0.310 mg/L. The mean value of the degree of contamination (Dc) in the surface waters of the N'djili basin is greater than 3, indicating heavy contamination of these waters (Lukaya river, Matete river, N'djili river, Ntshuenge river, Ngwele river). The average values of for the trace metal pollution index (HPI) are below the threshold value of 100, so overall, these waters are not very polluted. Nevertheless, particularly high concentrations were observed in the waters of the Matete River, with values exceeding 100, indicating severe localized pollution. Correlation analysis between trace metals and HPI indicates that lead and cadmium are the main contributors to surface water toxicity in the N'djili basin. These results highlight the urgent need to develop targeted strategies to reduce pollution in order to preserve public health and aquatic ecosystems.